JASTIP Turki-Indonesia Via Instagram - Putri, Kinanti Talita; Prasetya, Eska Perdana (Jurnal Pengabdian Nusantara, 2023)
In this digital era, technology has a very important role in all aspects, including economic and social aspects. Social media is a technology that is very much found in society. Social media, especially Instagram, is often used by consumers as a medium for sharing text, visuals, photos, and other information. In addition, Instagram is now widely used as a medium for business promotion, including the jastip business. Jastip stands for entrusted services, which are used for buying and selling transactions between buyers and service owners who are usually in different cities or countries. In this article, the author will reflect and share information about his own business between Turkey and Indonesia, including how to communicate with consumers and how to promote it on Instagram.